Multiscale Geoelectrical Properties of the Rochechouart Impact Structure, France. (2nd September 2021) - Quesnel, Yoann; Sailhac, Pascal; Lofi, Johanna; Lambert, Philippe; Rochette, Pierre; Uehara, Minoru; Camerlynck, Christian
Abstract: The 205 Ma Rochechouart impact structure (France) is characterized by various impactite formations overlying the Hercynian crystalline basement. New constraints from downhole logging and surface electrical resistivity measurements along >100 m long profiles reveal that the top melt‐bearing breccia layer is more conductive and porous than the underlying melt‐poor breccia layer. The stratigraphy within the impactite and the transition with the basement are irregular at small (∼1–10 m) and medium (>100 m) scales, with vertical amplitude up to 40–50 m. At larger scale (>1 km), audio‐magnetotelluric observations are able to map the lateral and vertical extent of fracturing/brecciation in the basement, reaching 200 m below the surface nearby Chassenon, in the northern part of the structure. Our results also unveil that the impactite deposits and the brecciated basement of the Rochechouart impact structure may have been shifted laterally and vertically during the modification stage of the impact event through displacements of megablocks, which may be associated with the collapse of a central uplift. Plain Language Summary: The geological formations of the Rochechouart impact structure are mapped using geoelectrical measurements. The electrical properties of impacted rocks differ significantly from the non‐impacted rocks, thus allowing the imaging of the geological contrasts. Our geophysical study reveals the complex topography of the transition between the impactite and the crystalline basement formations at the bottom of such medium‐size impact structure. The lateral and vertical extent of brecciation/fracturation is also investigated using this method, unveiling possible megablocks emplacement throughout a general northward tilting of the crater, which challenges the expected structure of the crater. Key Points: All impactite formations of the Rochechouart impact structure have a clear electrical signature Large‐scale electrical investigations unveil a rough transition between impactites and unbrecciated basement, implying possible megablocks Fracturing/brecciation in the Rochechouart basement locally reaches depths larger than 200 m